Implementasi Data Mining Menggunakan Algoritma Apriori Dalam Menentukan Persediaan Barang (Studi Kasus: Toko Swapen Jaya Manokwari) - Jubita Dongga; Ana ` Sarungallo; Novalin Koru; Gabriella Lante (Universitas Islam Raden Rahmat, Malang, 2023)
Data mining is generally known as the knowledge discovery in database (KDD), a activity that involves the use of historical data to discover patterns, or links in large data collections. Data mining has been applied in various aspects, one of which is a transaction at the swapen jaya store. The store can study the interest of the buyers using the data mining to process the sales data at the swapen jaya store. The research analyzed the acquisition of the sales transactions at the swapen jaya store using Apriori data mining and algorithms. Apriori algorithm is one of the kind that defines the combination of itemset and the association's rules that the supporting and supporting value should be a full amount and a drink with 5% support and a cumulative value of 36% and the drinks and food support 11% and a confident value of 22%.